Os bons executores da lei: a polícia soberana como dispositivo central do estado de exceção brasileiro - Fernando Nogueira Martins Júnior (2016)
The current data regarding the Brazilian penal system are most calamitous: mass incarceration and overcrowding, high selectivity with race, class and age bias, high level of lethality on the part of the State agents, inexistence of fundamental rights and warranties for the criminalized and even for the majority of the population. To understand this state of affairs is primarily to investigate the most privileged articulator of the penal catastrophe: the security ostensive police – in Brazil, the Military Police. Modeled in its current characters by the civilian-military-business dictatorship of 1964, governed by a poorly democratic administrative Law and with its constitutional destination turned to maintaining the “public order” (term without a well defined signification), the Brazilian ostensive Police, acting on illegitimate philosophical and empirical basis, manages the penal selectivity, choosing who enters the secondary criminalization process having, as general parameters, the black skin, the peripheral neighborhood dweller, the adolescent or young adult. The degree of violence and anomie perpetrated by the Military Police as the main actor of the penal system is so massive that it is verified the true establishment of a permanent state of exception in Brazil, with a immense biopolitical operability, leaving every and each one of the citizens subject to the lack of limits of the power of a “sovereign police”. The Brazilian permanent state of exception, regarding the penal system, has identical traces as the ones found in National-Socialist Germany, fact that would urge every citizen to a legal and even illegal mobilization towards the extinction of the militarized and separate from the community police, in order to transfer public safety responsibilities to all the citizens, who would manage them as much democratically and horizontally as possible.